"Micronutrient Content in Plant, Its Uptake, and Crop Yield in Cauliflower–cowpea-Okra Cropping Sequence as Impacted by Graded Level of Boron Fertilization". Issue 14 (5th August 2020) - Bhupenchandra, Ingudam; Basumatary, Anjali; Datta, Samiron; Kanta Singh, Laishram; Bora, S. S.; Helena Devi, Soibam; Gogoi, Bhabesh; Kalita, Pallabi; Das, Juri; Tamuli, Babita
ABSTRACT: For assessing the effect of boron fertilization on the micronutrient concentration in plants, its uptake in edible portion and crop yield in cauliflower–cowpea-okra cropping sequence in an Inceptisol of North East India field experiments were conducted during the year 2015–17 at Horticultural Experimental Farm, Assam Agricultural University, Jorhat. Five graded levels of boron were applied (0, 0.5, 1.0, 1.5, and 2.0 kg ha −1 ) to cauliflower once in both the years to assess the direct effect of boron fertilization in soil while cowpea and okra were grown as a succeeding test crops to study the concomitant residual effects of boron fertilization in cauliflower–cowpea-okra cropping sequence. Recommended dose of NPK fertilizer along with FYM for each crops were uniformly applied. Among the different levels of boron, experimental findings revealed that application of 2 kg B ha −1 was found prominent in augmenting the highest content of micronutrients in plant parts while the control recorded the lowest content for all the three crops in the sequence. A highly significant positive correlation between the different micronutrients content in edible portion of crops were recorded except copper. Similarly, application of 2 kg B ha −1 exhibited the highest micronutrient uptake in edible portion of crops, crop yield, crop equivalent yield, nutrient use efficiencies, and benefit cost ratio for all the crops in the sequence. Multivariate analysis (PCA) exercised on micronutrients content in edible portion of crops explained up to 97.19% of total variance with two principal components.